Constitutional Court in Facing the Industrial Revolution 4.0 - Silalahi, Wilma; Hamzah, M. Guntur (International Journal of Global Community, 2020)
Technological development has an important role and cannot be separated from the development of law throughout the world which resulted in the Industrial Revolution in countries. The Industrial Revolution developed according to its era, which began with the Industrial Revolution 1.0 to the Industrial Revolution 4.0. The Indonesian people also do not want to be left behind with the countries in the world in facing the Industrial Revolution 4.0 era, so the government strongly supports the era of the Industrial Revolution 4.0. But an important problem faced by the Indonesian people is the problem of human resources or the challenge of talent development for the Industrial Revolution 4.0, while the field needs for human resources in the fields of data scientist, coding, and software development continue to increase. The Industrial Revolutionary Era was marked by everything digitalizing and automating. Therefore, Indonesian people must also be prepared to face this era and most importantly want to change their mindset in dealing with change, not shut down and willing to accept input or changes from outside, including the judiciary, The Supreme Court and the Constitutional Court have implemented a judicial system based on digital technology known as the Electronic Court (e-Court), namely justice services that implement the use of internet-based computer technology in providing justice services to the justice seekers community. For this reason, it is necessary to study how the Constitutional Court as a high state institution played a role in the 4.0 Industrial Revolution. The Constitutional Court and its human resources are ready to face and undergo the Industrial Revolution 4.0 by continuing to improve knowledge and skills and which are the core business of the Constitutional Court conducted with the ICT system based on Pancasila and the 1945 Constitution.